Implementasi Program Sekolah Sungai sebagai Sarana Edukasi Lingkungan dalam Peningkatan Kesadaran dan Pelestarian Ekosistem Sungai - Salsabila Ahmad; Nathania Candra Fadilla; Wirna Amalia; Sefira Dewi Nazarina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to analyze the implementation of the River School Program in Gunung Anyar Tambak as an effort in environmental education. A qualitative research method with a case study approach was used to delve deeper into this program. The research findings indicate that the River School Program has successfully increased public awareness, especially among the younger generation, of the importance of preserving river ecosystems. Through various educational activities and training, this program has not only changed people's behavior to be more environmentally conscious but has also built strong collaborative networks among various stakeholders. However, the program still faces several challenges such as limited resources. To ensure the sustainability of the program, there is a need to strengthen resources, develop curricula, increase community participation, monitor and evaluate, collaborate across sectors, develop innovations, and replicate the program in other areas. Overall, the River School Program has great potential to be a solution to environmental problems, especially related to river conservation, and provide broader benefits to society and the environment.